Opposite effects of a time-trial and endurance cycling exercise on the neural efficiency of competitive cyclists - Scholler, V.; Groslambert, A.; Pirlot, T.; Grappe, F. (European Journal of Applied Physiology, 2023)
Purpose Time-trial require cyclists to have an acute control on their sensory cues to regulate their pacing strategies. Pacing an effort accurately requires an individual to process sensory signals with efficacy, a factor that can be characterized by a high neural efficiency. This study aimed to investigate the effect of a cycling time-trial on neural efficiency in comparison to a low intensity endurance exercise, the latter supposedly not requiring high sensory control.